The Importance of Supraclavicular Lymph Node FNAC: Striking Prevalence of Major Pathologies in a Tertiary Care Private Practice (East West Medical College Journal, 2026)
Background: Supraclavicular lymphadenopathy is often a clinical indicator of serious underlying pathology. Fine Needle Aspiration Cytology (FNAC) is a simple yet highly effective diagnostic tool.Objective: To assess the diagnostic yield and prevalence of major pathologies in supraclavicular lymph node FNAC cases.Methods: A retrospective analysis of 110 supraclavicular lymph node FNACs performed in a private histopathology practice setting was conducted.Results: Among the 110 cases, 55 (50%) were tubercular lymphadenitis, 18 (16.4%) lymphomas, 19 (17.3%) metastatic carcinomas (small cell lung carcinoma, squamous cell carcinoma, adenocarcinoma), 10 (9%) metastatic papillary thyroid carcinomas, and 8 (7.3%) soft tissue tumors misdiagnosed clinically as lymph nodes.Conclusion: FNAC of supraclavicular lymph nodes revealed 100% prevalence of major pathology, reinforcing its critical role in early diagnosis and management, particularly in resource-limited settings.EWMCJ Vol. 14, No. 1, January 2026: 43-47